1995
DOI: 10.1074/jbc.270.41.24580
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation of the Human Granulocyte-Macrophage Colony-stimulating Factor Receptor α Subunit Is Essential for Ligand Binding and Signal Transduction

Abstract: The ␣ subunit of the receptor for human granulocytemacrophage colony-stimulating factor (GM-CSF) is a glycoprotein containing 11 potential N-glycosylation sites in the extracellular domain. We examined the role of N-glycosylation on ␣ subunit membrane localization and function. Tunicamycin, an N-glycosylation inhibitor, markedly inhibited GM-CSF binding, GM-CSF-induced deoxyglucose uptake, and protein tyrosine phosphorylation in HL-60(eos) cells but did not affect cell surface expression of the ␣ subunit as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Human GM-CSF exhibits variable N-linked glycosylation site occupancy, which plays an important role in its biological activity. Indeed, it has been demonstrated that there is an inverse correlation between biological activity and the extent of N-glycosylation, suggesting that N-linked glycans down-regulate the bioactivity of the molecule (36,37). The 85-kDa isoform of CD44 on hemopoietic cells, on the other hand, acts as a ligand for hyaluronan produced by endothelial cells when it is sulfated on O-linked oligosaccharides in response to TNF-␣ stimulation (38).…”
Section: Discussionmentioning
confidence: 99%
“…Human GM-CSF exhibits variable N-linked glycosylation site occupancy, which plays an important role in its biological activity. Indeed, it has been demonstrated that there is an inverse correlation between biological activity and the extent of N-glycosylation, suggesting that N-linked glycans down-regulate the bioactivity of the molecule (36,37). The 85-kDa isoform of CD44 on hemopoietic cells, on the other hand, acts as a ligand for hyaluronan produced by endothelial cells when it is sulfated on O-linked oligosaccharides in response to TNF-␣ stimulation (38).…”
Section: Discussionmentioning
confidence: 99%
“…The other consists of biological functions. Recent reports have provided evidence that N-linked glycosylation may be required for ligand recognition or signaling (27)(28)(29)(30). However, what role N-linked glycosylation plays in ligand binding and signaling remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Western analysis of parallel samples for actin ensured equal loading of cell lysates. The band corresponding to GM-CSF receptor a glycoprotein is broad because of glycosylation at multiple sites (43). Note the absence of GM-CSF receptor a in patient B but not her parents or control.…”
Section: (Not Shown) (B)mentioning
confidence: 99%